2010
DOI: 10.1519/jsc.0b013e3181dc4622
|View full text |Cite
|
Sign up to set email alerts
|

Movement-Production Strategy in Tennis: a Case Study

Abstract: The present case study fell within the framework of the "absolute approach of expertise" because it assesses a "truly exceptional individual" (Chi, MTH, Cambridge Handbook of Expertise and Expert Performance, London, United Kingdom: Cambridge University Press, 2006, pp. 121-130). This technique analysis examined the movement-production strategy used by a professional tennis player performing serve-return strokes. This research enabled us to establish the relation between tennis serve-return technique and succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 13 publications
0
9
0
12
Order By: Relevance
“…It was reported that players experienced a decrease in body mass and blood lactate while an increase in heart rate, perception of effort and salivary cortisol concentrations on a set-to-set basis during the match, which showed the increasing fatigue and stress male players had to cope with under real match scenario [ 15 , 16 ]. Meanwhile, the movement patterns [ 17 , 18 ] and the technical and tactical effectiveness of male players were also widely investigated [ 6 , 13 , 19 , 20 ]. The previous studies found that first and second serve capability (direction, speed and success), breakpoint opportunity, net point success and distance covered within the match were important predictors to their success and the differentiation of player types.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that players experienced a decrease in body mass and blood lactate while an increase in heart rate, perception of effort and salivary cortisol concentrations on a set-to-set basis during the match, which showed the increasing fatigue and stress male players had to cope with under real match scenario [ 15 , 16 ]. Meanwhile, the movement patterns [ 17 , 18 ] and the technical and tactical effectiveness of male players were also widely investigated [ 6 , 13 , 19 , 20 ]. The previous studies found that first and second serve capability (direction, speed and success), breakpoint opportunity, net point success and distance covered within the match were important predictors to their success and the differentiation of player types.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it was examined the ways in which the game is played, without employing any experimental manipulation. Therefore, the research design was based on an observational model, which ensured no interference with the natural context (Gillet et al, 2010;Gomes et al, 2011;Hughes et al, 2002;Nevill et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…výberovej reakcii. Táto reaktívna agilita v stolnom tenise je založená na prílete loptičky k súperovi a následnom zahájení úderu súpera (Gillet et al, 2010). Do načasovania pohybu je z časti zapojená aj anticipácia.…”
Section: Metodikaunclassified